In situ evidence for HPV 16, 18, 33 integration in cervical squamous cell cancer in Britain and South Africa. - Cooper, K (1991)
In a previous study three types of HPV signal were described in CIN. It was suggested that a type 1 signal represented episomal HPV while a type 2 signal represented integrated HPV; and a type 3 signal was indicative of both episomal and integrated HPV. To test this hypothesis 91 squamous cell cancers (SCC) of the cervix from Britain and South Africa were examined for HPV 6, 11, 16, 18, 31, 33, 35. Of the South African group (n = 69) 64% contained HPV types 16 (n = 29) and 18 (n = 15). The SCC in the British group (n = 22) contained HPV 16 and HPV 33 in 12 and three cases, respectively. Of the HPV positive biopsy specimens, 86% showed a type 2 signal in keratinising and non-keratinising tumours and the remainder a type 3 signal. Type 3 signal was present only in keratinising tumours. The presence of punctate signal in 100% of HPV containing SCC, together with localisation of HPV signal to sister chromatids in tumour cell mitotic figures in vivo, provides further evidence for type 2, and the punctate component of type 3 signal representing viral integration.